Prevalence Of Counterfeiting In Nigeria: Evaluating Consumersa Experience In South-Eastern And South-Western Nigeria (Global Journal of Human-Social Science, 2012)
This study was meant to investigate the prevalence of counterfeiting in Nigeria evaluating consumers experiences The study was a survey which reacted act to a number of consumers of products drawn in South-Western and South-Eastern Nigeria A total of 517 participants took part in the study diet of which 224 43 3 were males while 293 56 7 were females with a mean age of 35 59 yrs SD 12 58 Questionnaire format was utilized for data collection in the study Both the descriptive and inferential statistics were employed for data analysis The results revealed that more of the study participants indicated that most of the identified products in the study have their counterfeits available The results also revealed that based on the extent of availability of counterfeited products more of the study participants still expressed that the identified products are much available in Nigerian markets The only hypothesis stated and tested which stated that there would be significant difference between consumers in South-Western and South-Eastern Nigeria on extent of availability of counterfeited products was supported t 515 5 13 P 001 The results were discussed adequately It was therefore established that the issue of counterfeiting is real in Nigeria as expressed by selected consumers of products Some recommendations were offered in the study as mechanisms for controlling or eliminating counterfeiting Keywords Counterfeiting Products consumers South- Eastern Nigeria south-Western Nigeria
Keywords: Counterfeiting; Products; consumers; South- Eastern Nigeria; south-Western Nigeria